Evaluation of distal radial artery cross‐sectional internal diameter in pediatric patients using ultrasound. Issue 5 (21st March 2013) - Varga, Eliane Q.S.; Candiotti, Keith A.; Saltzman, Bruce; Gayer, Steven; Giquel, Jadelis; Castillo‐Pedraza, Catalina; Sanchez, Grace; Halliday, Norman; Polaner, David
Summary In this study, we measure the radial artery internal diameter (RAID) in children up to 4 years of age before and after the induction of anesthesia. A B‐mode portable color Doppler ultrasound was used to measure the RAID. Three sets of measurements were taken for each child before and after the induction of anesthesia and with the wrist in the neutral and dorsiflexed positions. The reliability of the mean value of the RAID in the three sets in 24 patients was established. There were discrepancies between the RAID and the proposed catheter size in some individuals, which may not only render placement difficult but also have potential for arterial injury. There are good reasons to measure the RAID in small children prior to insertion of an intra‐arterial catheter.